Investigations into the pathogenesis of Dengue virus infections of humans : the endothelium as a target - Kelly, Tara Anne (Trinity College (Dublin, Ireland). Department of Microbiology, 2001)
The pathogenesis of the disease Dengue Haemorrhagic Fever/Dengue Shock Syndrome has not been elucidated. This study investigated the effects of Dengue virus, serotype 2 infection on both the human cell line ECV304/T-24 and primary HUVEC, as an in vitro endothelial cell model system. Infection of ECV304/T-24 cells by DEN 2 resulted in a loss of viability of the cells and death by apoptosis. However, the cells recovered and were persistently infected by the virus. Infection was productive, with the release o f infectious viral progeny into the supernatant and maximum production was found at 48 hours post infection. Persistently infected cells secreted DEN 2 at lower titres. Viral antigen expression within infected ECV304/T-24 cells and HUVEC was investigated using indirect immunofluorescence analysis.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin